Primary Cilia–An Underexplored Topic in Major Mental Illness - Pruski, Michal; Lang, Bing (Frontiers in Psychiatry, 2019)
Though much progress has been made in recent years towards understanding the function and physiology of primary cilia, they remain a somewhat elusive organelle. Some studies have explored the role of primary cilia in the developing nervous system, and their dysfunction has been linked with several neurosensory deficits. Yet, very little has been written on their potential role in psychiatric disorders. This article provides an overview of some of the functions of primary cilia in signalling pathways, and demonstrates that they are a worthy candidate in psychiatric research. The links between primary cilia and major mental illness have been demonstrated to exist at several levels, spanning genetics, signalling pathways and pharmacology, as well as cell division and migration. The primary focus of this review is on the sensory role of the primary cilium and the neurodevelopmental hypothesis of psychiatric disease. As such, the primary cilium is demonstrated to be a key link between the cellular environment and cell behaviour, and hence of key importance in the considerations of the nature and nurture debate in psychiatric research.